2016
DOI: 10.11604/pamj.2016.23.70.8434
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of asthma control using asthma control test in chest clinics in Cameroon: a cross-sectional study

Abstract: IntroductionThe goal of asthma treatment is to obtain and maintain a good control of symptoms. Investigating factors associated with inadequately control asthma could help in strategies to improve asthma control. This study aimed to determine the prevalence and factors associated with inadequately controlled asthma in asthma patients under chest specialist care.MethodsA cross-sectional study was conducted from November 2012 to May 2013. Physician-diagnosed asthma patients aged 12 years and above were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
6
1
1
Order By: Relevance
“…Further, females show inadequate asthma control as compared to males in our study. This result is also supported by other findings, a study done in Cameroon finds that women were more likely to have inadequate asthma control [43]. It is also stated females were more likely to be diagnosed and suffer from asthma in which the physiologic mechanism for these differences are not well understood [49].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Further, females show inadequate asthma control as compared to males in our study. This result is also supported by other findings, a study done in Cameroon finds that women were more likely to have inadequate asthma control [43]. It is also stated females were more likely to be diagnosed and suffer from asthma in which the physiologic mechanism for these differences are not well understood [49].…”
Section: Discussionsupporting
confidence: 76%
“…The difference with these results could be the study area difference between the European and developing countries in which level of literacy and economic advancement facilitates asthma control in Europe [33]. Study reports in Nigeria and Cameroon also stated that asthma control was found to be unacceptably poor [42,43]. A crosssectional study done in Jimma using the same tool showed that almost three fourth (76.1%) of the patients had uncontrolled asthma [44].…”
Section: Discussionmentioning
confidence: 93%
“…However, asthma control in Africa has not been well studied. In a recent study from Cameroun, 42% of the study population had inadequately controlled asthma [ 29 ]. Similar studies from Nigeria, the Maghreb countries, and Ethiopia have reported uncontrolled disease in 82.9, 71.3, and 71.4% of asthmatics, respectively [ 21 , 30 , 31 ].…”
Section: Main Textmentioning
confidence: 99%
“…In developed countries, asthma is insufficiently controlled in 40–70% of patients [10, 11, 12]. Africa is no exception; in Cameroon, for example, 42% of adult asthmatics are inadequately controlled [13]. Factors known to influence asthma control include socio-demographic characteristics, psychosocial factors, asthma severity, adherence to treatment, drug inhalation technique, and exposure to infectious agents (especially viruses) and allergens (indoor and outdoor pollutants).…”
Section: Introductionmentioning
confidence: 99%